2020
DOI: 10.1177/1420326x20925521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative research on the air pollutant prevention and thermal comfort for different types of ventilation

Abstract: In this article, a comparative study on the outdoor air pollutant prevention and indoor thermal comfort for different types of ventilation was carried out. Both objective experiment, subjective experiment and computational fluid dynamics (CFD) simulation were conducted to investigate the differences in air pollutant prevention and thermal comfort between four common ventilation methods, namely supplying on the ceiling and returning on the ceiling (SC-RC), supplying on the ceiling and returning on the side wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Two seconds of inhalation, 2 s of expiration, and 1 s of pause were used in each trial's breathing cycle (Figure 4B). With a pulmonary ventilation rate of (6 L/min) for each breath, the breathing rate was roughly (12) breaths per minute. (0.51/2 s = 0.25 L/s = 15 L/min) was used to compute the instantaneous flow.…”
Section: Thermal Manikinmentioning
confidence: 99%
See 1 more Smart Citation
“…Two seconds of inhalation, 2 s of expiration, and 1 s of pause were used in each trial's breathing cycle (Figure 4B). With a pulmonary ventilation rate of (6 L/min) for each breath, the breathing rate was roughly (12) breaths per minute. (0.51/2 s = 0.25 L/s = 15 L/min) was used to compute the instantaneous flow.…”
Section: Thermal Manikinmentioning
confidence: 99%
“…10,11 The system (CC/MV) also works with a central control system to maintain a unified indoor environment in the occupied area, and this cannot satisfy all passengers as air is provided from a distance from the passengers and is mixed with polluted room air before entering the breathing areas of people. 12,13 Several review studies have demonstrated that there is strong and sufficient evidence for most diseases to establish the link between ventilation and air movement in buildings and the spread of pathogens such as SARS, highlighting the importance of indoor environmental control. 14 As a result, personal ventilation has the potential to achieve efficient air distribution that delivers clean air directly to the breathing areas and allows individual microclimate control at each workstation.…”
Section: Introductionmentioning
confidence: 99%
“…according to the aerodynamic characteristics and the temporal and spatial distribution of viruses and other pollutants in the air [51] . Airflow affects the sedimentation and diffusion of virus and other pollutants [52][53] . Not only can proper ventilation and good outdoor air proveto reduce the transmission of indoor pollutants and viruses through the air [54] , but also reasonable building space organization will effectively reduce the transmission of viruses in the community [55] .…”
Section: Design Mode--healthy Wind Environment In Buildingsmentioning
confidence: 99%
“…Conventional ventilation systems are designed to dilute indoor-contaminated air through intruding fresh air from the outside, maintaining indoor air quality and thermal comfort at a satisfactory level. 13 There are two categories of ventilation systems according to different driving forces: natural ventilation systems and mechanical ventilation systems. 14,15 However, due to the shortfall in the stable wind pressure, natural ventilation systems are usually used for auxiliary purposes.…”
Section: Engineering Control Against Virus Spread With Ventilation Symentioning
confidence: 99%